Violence Experienced by the Character Aletta in the Novel Alaskaletta by Didik Sabrullah - Nababan, Ruth Devi; Nasution, Ikhwanuddin; Marsella, Emma (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research discusses the violence experienced by the character Aletta in the novel Alaskaletta by Didik Sabrullah using Johan Galtung's theory of violence in the study of literary sociology. The method used in this research is a descriptive qualitative method. The data in this research are quotes from the novel Alaskaletta by Didik Sabrullah which depicts violence and discrimination through interactions between characters. Data collection techniques use library study techniques, listening techniques and note-taking techniques. The data in this research were analyzed using content analysis techniques and using a literary sociology approach. The data is presented in narrative form because each data is described based on the results of the research conducted. The results of the analysis show that Aletta experienced various forms of direct violence, including physical, verbal and psychological violence. The physical violence experienced by Aletta included slapping, pushing and other rough actions. Verbal violence manifests itself in the form of insults and insults, while psychological violence can be seen in threats, manipulation and harassment that demean Aletta's dignity. This research concludes that violence in various forms reflects injustice and domination in interpersonal and family relationships, and reflects cultural values that enable and justify acts of violence. This study underlines the importance of an in-depth understanding of the impact of violence in literary works and its relevance in a wider social and cultural context.